Analisis Faktor-Faktor Keselamatan Dan Kesehatan Kerja Konstruksi Di Masa Pandemi Covid-19 Pada Pembangunan Gedung Kuliah Terpadu Universitas Palangka Raya: Analysis Of Construction Occupational Safety And Health Factors In The Covid-19 Pandemic On The Construction Of Integrated Lecture Building, Palangka Raya University - Nomensen Roynaldo Sitompul; Waluyo Nuswantoro; Veronika Happy Puspasari (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The Covid-19 pandemic has disrupted various sectors, one of which is the construction sector. The spread of Covid-19 on construction projects can harm workers, the work environment, and also disrupt project implementation. This study aims to determine the K3 factors of construction during the Covid-19 pandemic and the dominant construction K3 factors during the Covid-19 pandemic in the construction of the Palangka Raya University Integrated Lecture Building. Data collection was carried out by distributing questionnaires directly to the construction project workers of the Palangka Raya University Integrated Lecture Building. The data obtained from the questionnaire was explained using factor analysis to obtain construction K3 factors and dominant K3 factors during the Covid-19 pandemic. The results of the factor analysis show that the K3 construction factors during the Covid-19 pandemic in the construction of the Palangka Raya University Integrated Lecture Building are the worker involvement factor, the K3 procedure application factor, and the worker communication factor. And the dominant construction K3 factor during the Covid-19 pandemic is the worker involvement factor, where this factor occupies factor 1 in the interpretation of the results